Education for Environmental Citizenship - Hadjichambis, Andreas Ch; dos Reis, Pedro Guilherme Rocha; Paraskeva-Hadjichambi, Demetra; Ariza, Marta Romero; Boeve-de Pauw, Jelle; Gericke, Niklas; Knippels, Marie Christine P.J; Christodoulou, Andri (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue includes 14 empirical, theoretical, methodological research articles and reviews in various fields considering EEC. It provided a platform for researchers to share their research work on the field of education for environmental citizenship, including aspects of civic engagement and civic participation, democratic action, social and environmental change, individual and collective actions, environmental actions, socio-political actions, environmental justice, inter- and intra-generational justice, and connectedness to nature.